The essential type directory a sourcebook of over 1,800 typefaces and their histories - Dawson, Peter (Black Dog & Leventhal Publishers, 2019)
The most comprehensive, practical, and beautiful directory of type, organized by type category -- Serif, San Serif, Display, and Script -- and covering all styles throughout history.The Essential Type Directory offers 1,800 examples of the best in type design, spanning almost 600 years of design history. From classics such as Garamond, Baskerville, Futura, and Helvetica, to more idiosyncratic recent creations such as Gotham and Filosofia, The Essential Type Directory features illuminating profiles of the most important and influential typefaces ever created. Organized by type category-Serif, Sans Serif, Display, and Script-each typeface is presented in uppercase and lowercase alphabetical letters, along with numbers, key punctuation marks, and symbols. This comprehensive guide also features profiles and interviews with leading designers and type foundries, as well as inspirational examples of graphic designs using specific typefaces.